U.S. – TALIBAN: COMPARATIVE ANALYSIS OF THE STAGES OF NEGOTIATIONS - G. G. Machitidze (Сравнительная политика)
The article presents a comparative analysis of the stages of the negotiation process between the United States and the Taliban. The different positions of the B. Obama and D. Trump administrations towards the Afghan peace process are also compared. The relevance of this study is determined by necessity to adequately assess the possibilities of Russia's participation in the settlement of the Afghan confl ict, taking into account the increase of its role in Afghan affairs. Demonstrating the evolution of the US approach to contacts with the Taliban, the author draws attention to the unwillingness of the Taliban to seek compromises. At the fi rst stage of the negotiation process, the Taliban, waiting for the US plan for the full withdrawal of its troops from Afghanistan, were ready to discuss only exchange of prisoners and the delisting of the Taliban from the UN sanctions list. At the second stage, discussions ended with illusory promises of the ceasefi re, the intra-afghan dialogue and the provision of guarantees that terrorists would not use Afghanistan against the United States, but the Taliban’s demand for the speedy withdrawal of all foreign troops from Afghanistan remained unchanged. Despite exhortations of the United States, offi cial Afghan authorities had every reason to consider themselves excluded from the negotiation process. Ultimately, Americans declared that the draft of the agreement was ready. However, the US president refused to continue negotiations with the Taliban, as the fi nal version of the agreement indicated that the Taliban were not yet ready to abandon contacts with al-Qaeda and provide all the necessary guarantees regarding the non-use of Afghan territory by foreign terrorists. The author points out errors made by the Trump administration in planning and conducting negotiations with the Taliban. The results of the study can be used by the profi le department of the Russian Ministry of Foreign Affairs in the practical implementation of the foreign policy course of the Russian Federation in the Afghan direction.